An interval fuzzy model for magnetic biomonitoring using the specie Tillandsia recurvata L. - Chaparro, Mauro Alejandro Eduardo (2015)
Studies of magnetic monitoring for assessing air pollution have been proposed as alternative and complimentary of chemical methods. Such magnetic studies provide measurements at low cost and relative promptness. In this work, we present and apply a methodology to build an interval fuzzy model, which calculates the Tomlinson pollution load index (PLI). The input variables for the model are magnetic parameters relative to magnetic concentration, grain size and mineralogy. The model aims to two purposes, on one hand, to calculate the values of PLI only using magnetic variables and, on the other hand, to analyze the relationship between magnetic and chemical variables. The studied dataset was obtained from measurements of the biomonitor Tillandsia recurvata L. in a Mexican urban area (Santiago de Querétaro). The best model was selected from a total of about half a million possible models using a fitness measure (RIF). The model yields a satisfactory approximation of the PLI data and it was concluded that PLI increases with relation to: an increase in concentration of magnetic materials, an additional contribution to the magnetic signal of paramagnetic materials, and an increase in size of magnetic grains.